GAMBARAN CAKUPAN PELAYANAN KESEHATAN PADA PENDUDUK PENDERITA HIPERTENSI SESUAI STANDAR DI PUSKESMAS TAMAN SARI TAHUN 2025 - Tiarma Talenta Theresia; Sri Lestari; Anisa Ferbiyanti Rusli; Alexander Kenneth Kurniawan; Cathreen Mulyani; Jennifer Sim; Maria Barbie Liem; Zivanka Natania; Hanarni Kubelinda; Jenifer Angela Gunawan; Julvyn Julvyn; Raissa Kyani Wijaya (Jurnal Dunia Kesmas, 2026)
Abstract: Overview Of Health Service Coverage For Residents With Hypertension According To Standards At Taman Sari Community Health Center In 2025. Background: Hypertension is a serious health problem because of its high prevalence, its often asymptomatic nature, and its potential to cause various complications. Hypertension is one of the most frequently diagnosed diseases in public health services. This condition indicates the need to strengthen control efforts, education, and standard health services for patients with hypertension. Objective: To describe the coverage of standard health services for people with hypertension at Taman Sari Primary Health Center in 2025. Method: This study used a descriptive observational method with a cross-sectional design based on secondary data from 2024–2025. The study was conducted at Taman Sari Primary Health Center from March 11 to March 16, 2026. Results: The coverage of standard health services for people with hypertension at the Taman Sari District level in 2025 reached 10,758 services out of a target of 10,700, or 100.54%, indicating that the district target was achieved overall. However, disparities among urban villages remained. Four urban villages did not meet the target: Krukut (43.16%), Maphar (48.54%), Taman Sari (55.92%), and Keagungan (55.39%). Compared with 2024, the overall district coverage slightly decreased from 101.65% to 100.54%. Factors affecting this condition included limited patient knowledge, a health education system that was still limited, and ineffective recording media. Conclusion: Overall, the target coverage of hypertension services in Taman Sari District was achieved in 2024 and 2025, but equitable distribution of services across sub-districts remains suboptimal. Improvements can be made through the "SEHATI TAMAN SARI" program, monitoring and evaluation of hypertension outcomes through cross-sectoral engagement, and the provision of hypertension control books to support ongoing patient monitoring.